Behaviour of soybean seedlings in situations involving cotyledon removal - Lapaz, Allan de Marcos [UNESP]; Santos, Luiz Felipe de Melo [UNESP]; Antonio, Gabriel Leonardi [UNESP]; Vera, João Henrique Silva [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP] (My University, 2020)
Cotyledons have photosynthetic and reserve functions. In initial development, cotyledon herbivory makes the majority of species more susceptible to the environment. This study aimed to reproduce herbivory situations occurring in the field, caused by insect pests, through manual partial and total removal of the cotyledons, in order to evaluate the deleterious effects on the initial development of soybean [Glycine max (L.) Merrill]. The experimental design was completely randomized and arranged in a 2 × 3 factorial scheme, with two soybean cultivars (BMX Potência RR and Syngenta 1562 IPRO) and three situations involving removal of cotyledons (0%, 50% and 100%) in four replications, totalling 24 experimental plots. The partial or total removal of cotyledons caused a reduction in parameters related to the growth and initial development of soybean (stalk diameter, shoot length, root primary length, shoot dry mass and root dry mass), which is probably due to the nutritional and morphological changes documented in this study. In general, the Syngenta 1562 IPRO cultivar was more sensitive to cotyledon removal than the BMX Potência RR cultivar.
Keywords: Glycine max (L.) Merrill; Initial development; Morphophysiology; Nutrients